Towards a dendrochronologically refined date of the Laacher See eruption around 13, 000 years ago. (1st February 2020) - Reinig, Frederick; Cherubini, Paolo; Engels, Stefan; Esper, Jan; Guidobaldi, Giulia; Jöris, Olaf; Lane, Christine; Nievergelt, Daniel; Oppenheimer, Clive; Park, Cornelia; Pfanz, Hardy; Riede, Felix; et al.
Abstract: The precise date of the Laacher See eruption (LSE), central Europe's largest Late Pleistocene volcanic event that occurred around 13, 000 years ago, is still unknown. Here, we outline the potential of combined high-resolution dendrochronological, wood anatomical and radiocarbon ( 14 C) measurements, to refine the age of this major Plinian eruption. Based on excavated, subfossil trees that were killed during the explosive LSE and buried under its pyroclastic deposits, we describe how a firm date of the eruption might be achieved, and how the resulting temporal precision would further advance our understanding of the environmental and societal impacts of this event. Moreover, we discuss the relevance of an accurate LSE date for improving the synchronization of European terrestrial and lacustrine Late Glacial to Holocene archives. Highlights: Previous age estimates of the Laacher See Eruptions (LSE) around 12, 900 years are still diverging and imprecise. The combination of dendrochronology, wood anatomy, and  14 C measurements holds the potential to establish a precise LSE date. An absolute calendric date of the LSE would improve the synchronization of European Late Glacial to Holocene archives.